The Influence of Digital Payment Convenience and Cashless Promotion on Tourist Purchase Frequency with Perceived Ease of Transaction in Tourist Areas in Bogor - Sulistyo Budi Utomo (Westscience Press, 2026)
This study examines the impact of digital payment convenience and cashless promotions on tourists' purchase frequency and perceived transaction convenience in a tourist area in Bogor, Indonesia. The research employs a quantitative approach with a sample size of 225 tourists, using a structured questionnaire based on a Likert scale. Data analysis was performed using Structural Equation Modeling (SEM-PLS 3) to test the hypothesized relationships. The results show that both digital payment convenience and cashless promotions significantly influence tourists' purchase frequency and perceived transaction convenience. Specifically, digital payment convenience positively affects both purchase frequency and transaction convenience, while cashless promotions enhance both purchase frequency and transaction convenience. Additionally, perceived transaction convenience mediates the relationship between digital payment convenience and purchase frequency. These findings provide practical insights for tourism businesses looking to improve the customer experience and increase revenue by integrating digital payments and offering attractive cashless promotions.